-6n+16-3n+9=n-40

Simple and best practice solution for -6n+16-3n+9=n-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6n+16-3n+9=n-40 equation:


Simplifying
-6n + 16 + -3n + 9 = n + -40

Reorder the terms:
16 + 9 + -6n + -3n = n + -40

Combine like terms: 16 + 9 = 25
25 + -6n + -3n = n + -40

Combine like terms: -6n + -3n = -9n
25 + -9n = n + -40

Reorder the terms:
25 + -9n = -40 + n

Solving
25 + -9n = -40 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
25 + -9n + -1n = -40 + n + -1n

Combine like terms: -9n + -1n = -10n
25 + -10n = -40 + n + -1n

Combine like terms: n + -1n = 0
25 + -10n = -40 + 0
25 + -10n = -40

Add '-25' to each side of the equation.
25 + -25 + -10n = -40 + -25

Combine like terms: 25 + -25 = 0
0 + -10n = -40 + -25
-10n = -40 + -25

Combine like terms: -40 + -25 = -65
-10n = -65

Divide each side by '-10'.
n = 6.5

Simplifying
n = 6.5

See similar equations:

| r/14=13 | | 5m-4=2m+23 | | 5/7x=105 | | r^2+8r-0=20 | | d+118=907 | | 85x-4-9x=18+76x-22 | | 5/9(86-32) | | -4x+8x-5=4(x-1)-17 | | 71.43x=105 | | 3k+9=30 | | 4(y-5)+2=5 | | 3(3x+9)=9-2(x-9) | | 21p=819 | | s=bd-9 | | r/11=20 | | 3/8-5/15 | | 2c+8=-10c | | y=2x+45 | | 23-5x=32 | | 6-9x=7x+8 | | 3(5+x)=3 | | 88-1/3x9 | | 24=s/-22 | | 4-x-3x=-8 | | 3/4w-12w-4=12 | | 2x-4(3-2x)=4(x-5)-28 | | 150w+2=195w+1 | | 432=27v | | 6y/2y | | 8-.6(6-15-7)+7= | | 7/(2/3) | | y+1=16 |

Equations solver categories